The Music-Hall Actress and Transcending Femininity in the Victorian Public Sphere: A Re-Orientation of Her Moral Status. - Pettersson, Lin Elinor (Instituto Universitario de Estudios de las Mujeres (IUEM), 2022)
The actress, like the prostitute, was one of the female figures who in the nineteenth century bore a certain social stigma for being professionally active in public and non-domestic roles that were considered vulgar and immoral. This prejudiced view is indebted to the ideology of separate spheres, which has proven to be both class-bound and unstable. While critics as Davis (1991) and Kift (1996) have questioned the overgeneralised association between actresses and prostitutes, feminist scholars have challenged the strict separation of gendered spheres, and argued for the instability and fluidity of this spatial divide. Taking this as a starting point, this essay addresses the Victorian popular actress from a feminist perspective to explore the transcendental role she had in music-hall culture. I will explore how this popular entertainment developed from a working-class culture and question the applicability of bourgeoise values and the ideology of separate spheres to the music hall. In doing so, I hope to shed new light over the music-hall actress as a working woman demonstrating that she was better esteemed than previously admitted, and argue that she turned the music hall into a space of self-fulfillment though subversion and transcendence of female roles.
Keywords: Teatro de variedades - S. XIX; Mujeres - S. XIX - Situación social; Actress; Music hall; Transcending; Victorian popular entertainment; Public/private dichotomy; Victorian women